Blocking the Leukotriene B4 Receptor 1 Inhibits Late-Phase Airway Responses in Established Disease - Waseda, Koichi (American Thoracic Society, 2011)
Most of the studies investigating the effectiveness of blocking the leukotriene B4 (LTB4) receptor 1 (BLT1) have been performed in models of primary or acute allergen challenge. The role of the LTB4-BLT1 pathway in secondary challenge models, where airway hyperresponsiveness (AHR) and airway inflammation have been established, has not been defined. We investigated the effects of blocking BLT1 on early- and late-phase development of AHR and airway inflammation in previously sensitized and challenged mice. Female BALB/c mice were sensitized (Days 1 and 14) and challenged (primary, Days 28–30) with ovalbumin. On Day 72, mice were challenged (secondary) with a single OVA aerosol, and the early and late phases of AHR and inflammation were determined. Specific blockade of BLT1 was attained by oral administration of a BLT1 antagonist on Days 70 through 72. Administration of the antagonist inhibited the secondary ovalbumin challenge–induced alterations in airway responses during the late phase but not during the early phase, as demonstrated by decreases in AHR and in bronchoalveolar lavage neutrophilia and eosinophilia 6 and 48 hours after secondary challenge. The latter was associated with decreased levels of KC protein, macrophage inflammatory protein 2, and IL-17 in the airways. These data identify the importance of the LTB4-BLT1 pathway in the development of late–phase, allergen-induced airway responsiveness after secondary airway challenge in mice with established airway disease.